Flux Ratios for Effects of Permanent Charges on Ionic Flows with Three Ion Species: Case Study (II) (Journal of Mathematical Study, 2024)
In this paper, we study effects of permanent charges on ion flows throughmembrane channels via a quasi-one-dimensional classical Poisson-Nernst-Planck system. This system includes three ion species, two cations with different valences andone anion, and permanent charges with a simple structure, zeros at the two end regions and a constant over the middle region. For small permanent charges, our maingoal is to analyze the effects of permanent charges on ionic flows, interacting with theboundary conditions and channel structure. Continuing from a previous work, weinvestigate the problem for a new case toward a more comprehensive understandingabout effects of permanent charges on ionic fluxes.